Perancangan Sistem Informasi Keuangan Politeknik Unisma Malang - Moch. Fahmi Reza; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Politeknik Unisma Malang is a vocational education institution that was established on March 27, 2002 SK MENDIKNAS RI No. 19/D/O/2002 and No. 472/D/T/2003 which is located at Jl. MT. Haryono No. 193 Malang. The financial officer of the Poluteknik Unisma Malang has used computer facilities in processing student financial data, but the tool used is a non-integrated spreadsheet application. This resulted in the task of entering new student data which should have been carried out by the registration officer, carried out by the finance officer. In addition, the process of processing billing data, payment and preparing students financial report becomes complicated because the data is stored on multiple worksheets. To overcome this problem, an information system is needed that can process and make reports on student financial data, so in this research the design of a financial information system was carried out. In this research, the waterfall model is used in developing a system that contains steps that are carried out sequentially. Only 2 stages were carried out in this research. The first stage is the requirements definition which produces 7 features, 18 functional requirements, 1 non-functional requirement, and 19 use cases. The second stage is system and software design which produces system architecture design, analysis class from use case, unification of analysis class, package, class diagram, sequence diagram, data modeling, element of design, interface design, and interface prototype. The research ends with testing the design using a traceability matrix which states that all requirements can be traced to features, use cases, and sequence diagrams. In addition, testing of the interface prototype was also carried out using compatibility testing which resulted in that the prototype interface created could be opened in various browsers.